2017
DOI: 10.14218/jerp.2016.00036
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Chemodiversity in Extracts and Essential Oil of Melaleuca viminalis and Melaleuca armillaris of Myrtaceae Family

Abstract: Background and objective: Melaleuca viminalis (syn. Callistemon viminalis, red bottle brush) and Melaleuca armillaris (white Bottle brush) belong to the family Myrtaceae and are reported for their traditional medicinal properties. The objective of this study was to explore and compare the chemical compositions and biological properties of these two species.Methods: Sequential extraction and hydro-distillation methods were employed to extract essential oils for further analysis of chemical composition by gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…glycoside: kaempferol 7-methyl ether 3-O-β-D-glucopyranoside (9), kaempferol 4′ methyl ether 3-O-β-D-glucopyranoside (10), kaempferol 3-O-β-D-glucuronopyranoside (13) kaempferol 3-O-β-D-rhamnopyranoside (14) [35][36][37], four quercetin glycoside viz quercetin 3-O-β-D-xylopyranosyl-(1‴→2″)-O-β-D-glucopyranoside (7) [38,39], isoquercetin (15), quercitrin (16), quercetin 7-O-β-D-glucopyranoside (17) [35][36][37], five phenolic acid viz chlorogenic acid (6) [40], ellagic acid (8) [41], gallic (11), methyl gallate (12) [42], caffeic acid [40], (18) as well as two aglycones, kaempferol (19) and quercetin (20) [36]. All compounds were isolated from C. viminalis aerial parts for the first time except (8, 11-12, 15-16, and 20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…glycoside: kaempferol 7-methyl ether 3-O-β-D-glucopyranoside (9), kaempferol 4′ methyl ether 3-O-β-D-glucopyranoside (10), kaempferol 3-O-β-D-glucuronopyranoside (13) kaempferol 3-O-β-D-rhamnopyranoside (14) [35][36][37], four quercetin glycoside viz quercetin 3-O-β-D-xylopyranosyl-(1‴→2″)-O-β-D-glucopyranoside (7) [38,39], isoquercetin (15), quercitrin (16), quercetin 7-O-β-D-glucopyranoside (17) [35][36][37], five phenolic acid viz chlorogenic acid (6) [40], ellagic acid (8) [41], gallic (11), methyl gallate (12) [42], caffeic acid [40], (18) as well as two aglycones, kaempferol (19) and quercetin (20) [36]. All compounds were isolated from C. viminalis aerial parts for the first time except (8, 11-12, 15-16, and 20).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several phloroglucinol compounds were identified [8][9][10]. Moreover, some studies have demonstrated that the alcoholic extracts of the leaves, aerial parts, flower, bark, and fruits of C. viminalis possessed different biological activities as cytotoxic [5,11,12], antioxidant [6,7,[11][12][13][14][15], hepatoprotective [6], antidiabetic [16], and analgesic activities [17]. Reactive oxygen species (ROS) are generated by different physiological processes and they have important functions in organisms; one of them is the defense function, as shown in the activation polymorphonuclear neutrophils by exogenous or endogenous motivations, which is followed by increasing the oxygen consumption and ROS production cascade leading to generation of other free radicals as superoxide anion (O 2 − ) and hydrogen peroxide (H 2 O 2 ) [18].…”
Section: Introductionmentioning
confidence: 99%